Carbene-like reactivity of methoxy groups in a single crystal SAPO-34 MTO catalyst. Issue 7 (25th February 2022) - Minova, Ivalina B.; Bühl, Michael; Matam, Santhosh K.; Catlow, C. Richard A.; Frogley, Mark D.; Cinque, Gianfelice; Wright, Paul A.; Howe, Russell F.
Abstract : In situ synchrotron infrared microspectroscopy on single crystals of SAPO-34 reveals that a carbene insertion mechanism is responsible for the first carbon–carbon bond formation from surface methoxy groups. Abstract : Synchrotron FTIR microspectroscopy coupled with mass spectrometric analysis of desorbed products has been used to investigate the initial stages of the methanol to olefins (MTO) reaction in single crystals of SAPO-34. Surface methoxy groups (SMS) are key to initial dimethylether (DME) and subsequent carbon–carbon bond formation. Deprotonation of SMS is the critical first step in direct olefin formation at low temperatures and DME is not involved in the carbon–carbon forming step. Experiments with CD3 OH confirm the deprotonation step and show an inverse kinetic isotope effect consistent with irreversible deprotonation. The subsequent formation of alkoxide species, which are the precursors of the olefinic hydrocarbon pool present in working MTO catalysts, is initiated via insertion of surface carbene-like species into adjacent SMS. The observed induction period for this process is determined by the limited mobility of SMS and/or carbene species. Olefins formed from cracking of the alkoxide species then transmit carbon–carbon bond formation through the SAPO-34 by rapid diffusion and reaction with further SMS. Acetyl species seen with methanol at higher temperatures support the insertion of CO into SMS suggested in the literature, but these species do not play a role in direct olefin formation.